2013
DOI: 10.1111/jonm.12166
|View full text |Cite
|
Sign up to set email alerts
|

Quality of work life as a predictor of nurses' intention to leave units, organisations and the profession

Abstract: The study provides important information to nurse administrators about the aspects of QWL that most commonly lead nurses to leave their units, organisations, and even the profession itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 34 publications
6
66
1
4
Order By: Relevance
“…Nurses working in wards and emergency or intensive care units (usually involving shift work, direct patient care and high time pressure) reported lower QoL (Chiu et al., ). Quality of work life as a whole has been strongly associated with nurses’ intention to leave, with lower quality of work‐life related to greater intention to leave (Almalki, FitzGerald, & Clark, ; Lee Dai et al., , Lee et al., ). However, the relationship between quality of life and intention to leave nursing or midwifery remain uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Nurses working in wards and emergency or intensive care units (usually involving shift work, direct patient care and high time pressure) reported lower QoL (Chiu et al., ). Quality of work life as a whole has been strongly associated with nurses’ intention to leave, with lower quality of work‐life related to greater intention to leave (Almalki, FitzGerald, & Clark, ; Lee Dai et al., , Lee et al., ). However, the relationship between quality of life and intention to leave nursing or midwifery remain uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…For their parts, external dimensions included: (1) user demands, (2) healthcare policy, and (3) the labour market. Based on O'Brien-Pallas and Baumann's model of QWL, Lee, Dai and McCreary [23] have developed their own conceptual framework for Chinese QWL scale. They have established significant positive relationships evidence of nurses' QWL between economic context, work environment, supportive milieu, professional recognition, workload, teamwork, and autonomy of nurses (r = 0.72, p < .01).…”
Section: Overview Of the Scientific Literature On Qwl In The Disciplimentioning
confidence: 99%
“…[11,22] For example, the NMs' administrative role consists of hiring and evaluating the performance of staff nurses, developing departmental budgets, and maintaining inventory of medicines, equipment, and nursing supplies. [11,[20][21][22][23][24] As to the clinical role of NMs, they must be able to mentor nurses' clinical practice, develop education programs, and contribute to the staff's professional development. [20] For example, NMs also use strategies for risk anticipation and assessment to design, implement, and evaluate plans of care for a cohort of patients in a context of infection outbreaks.…”
Section: Nms' Scope Of Practicementioning
confidence: 99%
“…Therefore, the above hypothesis is rejected. Based on this studies have been reported by Lee et al (2015).…”
Section: The Findings Of Seventh Sub-hypothesesmentioning
confidence: 68%